PENERAPAN E-OFFICE SIPSMART DI UNIVERSITAS SEBELAS MARET - Daniel Indra Wijaya; Patni Ninghardjanti; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
The purpose of this study was to determine the application of the SIPSMART e-office at Sebelas Maret University. The research method used is qualitative with a case study approach. Researchers present descriptive data in the form of informants or sources, field observations. Sources of data are informants, activities or events, as well as documentation or archives. The sampling technique was carried out using purposse sampling. Researchers in this study used triangulation of sources and methods in testing the validity of research data. The data analysis technique used in this research is interactive model data analysis. The SIPSMART application is used to store student achievement data which later the output from SIPSMART can be used for students as evidence of their achievement while being a student. The implementation of the SIPSMART e-office at Sebelas Maret University Surakarta has not been perfect, it can be seen from the steps that have been done have not yet yielded maximum results. Although the implementation of SIPSMART has been carried out through the planning and implementation stages. The planning stage consists of student competence and also server creation. Meanwhile, the implementation stage of the launching activity and also socialization. The socialization activities carried out were not concurrent at all levels of students, because the socialization conducted was only a few students, so that the information conveyed did not spread, so some students, staff, and lecturers still did not understand SIPSMART.